Kidney Allograft and Recipient Survival After Heart Transplantation by Induction Type in the United States. Issue 3 (March 2022) - Riad, Samy; Alexy, Tamas; Jackson, Scott; Goswami, Umesh; Martin, Cindy
Abstract : Background: Induction choices for kidney-after-heart transplant recipients are variable. We examined the impact of kidney induction types on kidney graft and patient survival in heart transplant recipients. Methods: We analyzed the Scientific Registry of Transplant Recipient database from inception through the end of 2018 to study kidney and patient outcomes in the United States after heart transplantation. We only included recipients who were discharged on tacrolimus and mycophenolate maintenance. We grouped recipients by induction type into 3 groups: depletional (N = 307), nondepletional (n = 253), and no-induction (steroid only) (n = 57). We studied patients and kidney survival using Cox PH regression, with transplant centers included as a random effect. We adjusted the models for heart induction, recipient and donor age, gender, time between heart and kidney transplant, heart transplant indication, HLA mismatches, payor, live-donor kidney, transplant year, dialysis status, and diabetes mellitus at the time of kidney transplant. Results: The 1-y kidney rejection rates and creatinine levels were similar in all groups. The 1-y rehospitalization rate was higher in the depletional group (51.7%) and nondepletional group (50.7%) than in the no-induction group (39.1%) although this was not statistically significant. There were no differences in recipient or kidney survival by kidney induction type. Live-donor kidney was associated with improved patient (hazard ratio, 0.74; 95% confidence interval, 0.54-1.0; P = 0.05) and kidney survival (hazard ratio, 0.45; 95% confidence interval, 0.24-0.84; P = 0.012]. Conclusions: Type of kidney induction did not influence patient or kidney graft survival in heart transplant recipients. No-induction may be the preferred choice due to the lack of clinical benefits associated with induction use.